Model Pengelolaan Bank Sampah Sebagai Basis Ekonomi Sikular di Provinsi Sumatera Utara: Dalam Pembahasan Maqashid Syariah - Sri Herlina; Muhammad Ramadhan; Isnaini Harahap (CV. Creative Tugu Pena, 2026)
Waste management challenges continue to escalate and require a management model that not only focuses on environmental sustainability but also generates social, economic, and religious benefits. This study aims to formulate a Maqashid Sharia-Based Waste Bank Management Model to improve community welfare in North Sumatra. The research was conducted at three central waste banks in North Sumatra using a quantitative approach. Quantitative data were collected from 94 respondents and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). This study examines four key waste bank management variables: governance (X1), community participation (X2), waste bank institutional capacity (X3), and government policy support (X4), and their influence on community welfare based on Maqashid Sharia (Y). The findings indicate that waste bank management in North Sumatra contributes positively to Maqashid Sharia-based community welfare, particularly in the Hifz al-Mal dimension through increased income and improved economic resilience. Waste banks also support Hifz ad-Din, Hifz an-Nafs, Hifz al-'Aql, and Hifz an-Nasl through the strengthening of religious values, environmental health, community education, and intergenerational sustainability. These dimensions of maqashid sharia are interconnected and mutually reinforcing, resulting in holistic and sustainable public benefit (maslahah). The SEM-PLS analysis demonstrates that the four waste bank management variables significantly influence community welfare based on Maqashid Sharia. Waste bank governance (X1) and community participation (X2) exhibit strong effects, waste bank institutional capacity (X3) exhibits a weak effect, and government policy support (X4) exhibits a moderate effect. The future development of waste banks in North Sumatra should focus on sustainable governance transformation, strengthening inclusive community participation, developing professional and digitally enabled institutions, and implementing integrated performance-based policies through multi-stakeholder collaboration and data-driven evaluation systems. This study proposes the SMART-WASTE Governance Model (Sustainable, Maqashid-Based, Adaptive, Resilient, and Transformative Waste Governance) as an integrated framework that combines Maqashid Sharia principles, sustainable governance, community participation, institutional strengthening, circular economy practices, and government policy support within an integrated waste bank management system. The model is designed to be adaptive, resilient, transformative, and oriented toward improving community welfare.